Cauda Equina Paraganglioma: A Report of a Rare Case and Review of Literature - Mukesh Shukla; Jayesh Sardhara; Kuntal Kanti Das; Chaitanya Godbole; Sushila Jaiswal; Awadhesh Jaiswal; Sanjay Behari (Indian Journal of Neurosurgery)
Abstract Extra-adrenal paragangliomas (EAPs) are benign tumors of neuroendocrine origin. These tumors mostly arise from the carotid body and the jugular bulb area. EAP affecting the spine and filum terminale, known as cauda equine paraganglioma is rarely encountered in clinical practice. In this report, we present a case of a 28-year-old lady with paraganglioma at L2/3 level who presented with low back pain with radiation of pain to both legs for 4 year duration. The patient underwent L2/3 laminoplasty with total excision of tumor. Following surgery, backache and radicular pain subsided completely. We discuss the case and present a review of other cases reported in the literature.